Diversification of Malaysian art (1990s- 201Os) - Abdullah, Sarena (Srinakharinwirot University Bangkok, Thailand, 2014)
The development of arts in Malaysia during the 1970s and the 1980s has been directly or indirectly influenced by the Malaysian government policy since late 1969s. As a result, the development of Malaysian art during the two decades were highly influenced by the National Economic Policy (NEP), National Cultural Policy and the subsequent Islamization Policy spearheaded by the government.